PERUBAHAN PENGGUNAAN TANAH PERTANIAN MENJADI NON PERTANIAN (ALIH FUNGSI TANAH) DI KABUPATEN WONOGIRI (STUDI DI KECAMATAN SELOGIRI, KABUPATEN WONOGIRI) - Asrie Fajarrani Hadipitoyo, Ana Silviana*, Sri Sudaryatmi (Diponegoro Law Journal, 2013)
The increasing population and the increasing activity of the population will result in increased demand resulted in a change of land use from agricultural land to non-agricultural. Selogiri districts, is one example of the agricultural area in accordance with Regulation of Wonogiri Number 9 Year 2011 on Spatial Planning Wonogiri’s Years 2011-2031, but more land is converted to non-agricultural use.The results showed many irregularities that occurred during the licensing process conversion of agricultural land into non-agricultural in Wonogiri. The deviation permits decision includes refusal of land use change only verbally, the licensing process takes a long time, there is an extra cost and there are no provisions beyond strict sanctions against the violation of land-use change permit. Therefore, changes in agricultural land use impacts are far more negative than positive impacts resulting in damage to the environment and people's mindsets changed from productive to consumptive. There are some efforts to control land use changes made by the government, such as creating and disseminating new regulations, tighten the licensing process and improve the performance of village officials.